The Effect of Financial Performance, Tax Avoidance, and Investment Opportunity Set on Firm Value in The Agricultural Sector - Riffulin Ni’matul Ishlah; Khairina Natsir (Graduate Program of Universitas Tarumanagara, 2023)
This study aims to investigate verifiable data regarding the effect of profitability, liquidity, leverage, tax avoidance, and investment opportunity set on the firm value of the agricultural sector companies listed on the Indonesia Stock Exchange from 2017 until 2020 period. This study is descriptive research using quantitative data and purposive sampling is used to limit the research object to specific criteria. The research sample included 24 companies with 96 observational data. The panel data regression model will be used for the data analysis, which will be processed with the E-views 9.0 software. The results show that the variables of profitability and tax avoidance have a positive and insignificant effect on firm value, while liquidity, leverage, and investment opportunity set have a positive and significant effect on firm value.